1997
DOI: 10.1016/s0022-5347(01)65306-0
|View full text |Cite
|
Sign up to set email alerts
|

Visual Erotic Stimulation Test for Initial Screening of Psychogenic Erectile Dysfunction: A Reliable Noninvasive Alternative?

Abstract: A positive response to visual erotic stimulation is strongly indicative of a predominantly psychogenic cause of erectile dysfunction. In combination with patient sexual history and pharmacological erection testing, visual erotic stimulation can be performed as an initial, minimally invasive test for cost-effective screening of psychogenic impotence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…They reported that in 32 patients with normal erotic erections, the compatibility ratio with nocturnal erection was 63%, while in 105 patients with abnormal erotic erections, the compatibility ratio was 47%. Martins and Reis [11] reported that in a total of 76 patients the AVSS test using the RigiScan discriminated psychogenic ED with 71% sensitivity and 96% specificity. However, to our knowledge, no comparative studies between the findings of AVSS and NPT tests using the RigiScan system have been previously reported in the English literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that in 32 patients with normal erotic erections, the compatibility ratio with nocturnal erection was 63%, while in 105 patients with abnormal erotic erections, the compatibility ratio was 47%. Martins and Reis [11] reported that in a total of 76 patients the AVSS test using the RigiScan discriminated psychogenic ED with 71% sensitivity and 96% specificity. However, to our knowledge, no comparative studies between the findings of AVSS and NPT tests using the RigiScan system have been previously reported in the English literature.…”
Section: Discussionmentioning
confidence: 99%
“…The videotape material used in this study included a selection of various types of sexual stimuli assembled from several commercial films of heterosexual activity with sound. A normal erectile response to AVSS included rigidity of 70% or greater at tip and base of the penis [11].…”
Section: Methodsmentioning
confidence: 99%
“…Several adaptations for NPT monitoring were described to reduce the cost of nocturnal sleep laboratory testing and/or to improve the diagnostic efficiency of tumescence monitoring. These include monitoring during the following: 1) morning naps preceded by modest sleep deprivation (229,230); 2) audiovisual and/or fantasy stimulation (231)(232)(233); 3) erectile response to intracavernous vasoactive drug administration with or without audio-visual enhancement (230); 4) pulse Doppler analysis of penile arteries with audio-visual enhancement of the erectile response (234,235); 5) erotic audiovisual enhancement of the erectile response to vibrotactile stimulation (236); and 6) affective and cognitive response to erotic audio and fantasy stimulation (237). However, several pitfalls of real-time tumescence and rigidity testing in its present form exist and need to be addressed before a suitable adaptation for general screening can be recommended.…”
Section: June 2001mentioning
confidence: 99%
“…However, the traditional AVSS test may experience a low response rate or high false negative response rate induced by inadaptable testing surroundings, the subject’s psychological factors, and poor sexual arousal to a conventional monitor, which may limit its widespread application in clinical practice. 13 , 14 In Kim et al’s study, 14 the positive response rates (duration of average maximal rigidity ≥5 minutes) of conventional AVSS were 37% in normal men. Furthermore, only 3 (13.6%) of the 22 normal men sustained a penile rigidity of 70% or more for more than 5 minutes, and 10 (45.5%) had a rigidity of 40% or more.…”
Section: Discussionmentioning
confidence: 92%